VALUATION OF THE CONSUMPTIVE AND PRODUCTIVE USES OF WILD AND DOMESTICATED INDIGENOUS LEAFY VEGETABLES IN SOUTHEASTERN NIGERIA (2013)
Vegetables are grown for human consumption all over the world. Indigenous Leafy Vegetables (ILV), both wild and domesticated species make important contributions to household improvement in Nigeria. However, information on availability of these species in the market and the consumption level at household is limited. Therefore, ILV species in southeastern Nigeria were investigated in order to determine their availability and consumption level. Multi-stage random sampling procedure was adopted for selecting three states (Imo, Anambra, Ebonyi), three agricultural zones, communal and household levels. One rural and one urban community were purposively selected from each of the three Agricultural Development Programme zones. Existence of a central market formed the main criterion for selection of an urban community. Ten households were randomly selected and one market was surveyed in each community. Information on ILV species consumed and the corresponding expenditure during the week preceding the interview were collected from the households. Also information on ILV species on sale in the markets, prices and profit margins were obtained. Data were analysed using descriptive statistics and Z-test at p = 0.05. A total of 16 domesticated and 17 wild ILV species were commonly consumed (95% of the respondents) and marketed (average of 52±9.3 persons in each market surveyed) in the study area. These vegetables were consumed 2.0±0.6 times weekly with domesticated ILV accounting for 75.4% of the times. More than one vegetable species were usually used in meal preparation in the area. An average of 4.0±1.2 different species of vegetables were consumed by each household weekly with expenditures ranging between N182.60 and N227.76 in the rural areas and between N205.64 and N222.04 in the urban communities. Selling of the vegetables was a part-time occupation for majority (82.6%) of the traders in the rural, but full-time for 65.3% in the urban areas. The prices of the vegetables ranged between N42.43 and N181.22/kg in the rural and between N50.0 and N175.23/kg in urban markets except, Gnetum africanum which maintained an exceptionally high price that ranged between N498.22/kg and N933.33/kg in rural and between N222.17 and N929.77/kg in urban markets while remaining the most preferred wild ILV species. Each seller sold an average of 3.0±0.6 different species of vegetables with daily profit margins that ranged between N419.55±70.07 and N738.27±96.79 in rural and between N526.41±87.42 and N805.47±112.55 in urban markets. Profit margins were significantly higher (Z= -5.4) in urban than in rural markets. In the rural markets, profit margins of sellers of wild ILV (N205.34±95.84) were significantly higher (Z= 4.8) than for sellers of domesticated ILV (N175.96±75.89). In the urban markets, profit margins of sellers of domesticated ILV (N231.10±62.50) were significantly higher than for sellers of wild ILV (N 207.64±138.09). There was a high level of sales and consumption of indigenous leafy vegetable species in the study area. Domestication and commercialisation of Gnetum africanum will enhance the economic well-being of the respondents because of its high preference and market values. Keywords: Indigenous leafy vegetables, Vegetable consumption, Gnetum africanum Word Count: 481